Classical and Quantum Exact Solutions for a FRW Multiscalar Field Cosmology with an Exponential Potential Driven Inflation - J. Socorro; Omar E. Núñez; Rafael Hernández-Jiménez (Advances in Mathematical Physics)
A flat Friedmann-Robertson-Walker (FRW) multiscalar field cosmology is studied with a particular potential of the form V(ϕ,σ)=V0e-λ1ϕ-λ2σ, which emerges as a relation between the time derivatives of the scalars field momenta. Classically, by employing the Hamiltonian formalism of two scalar fields (ϕ,σ) with standard kinetic energy, exact solutions are found for the Einstein-Klein-Gordon (EKG) system for different scenarios specified by the parameter λ2=λ12+λ22, as well as the e-folding function Ne which is also computed. For the quantum scheme of this model, the corresponding Wheeler-DeWitt (WDW) equation is solved by applying an appropriate change of variables.